Instagram Captions Improve Descriptive Writing Performance in EFL Students - KHUSNIA; Wahyu Taufiq (Universitas Muhammadiyah Sidoarjo, 2025)
The rapid expansion of social media has transformed educational practices by introducing technology-mediated learning environments that are familiar to students. General Background: Social networking platforms are increasingly integrated into language education to support engagement and authentic communication. Specific Background: Instagram offers visual content and caption features that enable learners to produce descriptive texts based on images while interacting with peers and teachers. Knowledge Gap: Despite prior studies on social media in language learning, limited research has examined the use of Instagram captions combined with a student-centered approach in Indonesian secondary schools. Aims: This study investigated whether learning through Instagram captions improves students’ ability to write descriptive texts. Results: Using a quasi-experimental design with control and experimental groups, statistical analysis of pre-test and post-test scores showed that the experimental group achieved significantly higher writing scores than the control group. Instagram functioned as contextual media that supported idea generation, vocabulary development, and paragraph organization through active participation and feedback. Novelty: The study introduces the integration of Instagram caption writing within a student-centered framework at MA Islamiyah Candi Sidoarjo. Implications: Findings suggest that social media-based tasks can serve as practical alternatives for teaching descriptive writing and fostering active learning in English as a Foreign Language classrooms. Highlights: Experimental participants achieved higher post-test outcomes than the comparison group. Visual prompts and online interaction supported idea development and textual organization. Classroom activities encouraged active participation through peer feedback and revision. KEYWORDS: Instagram; Descriptive Writing; EFL Students; Student-Centered Learning; Social Media